Unveiling research landscapes on climate change education and curriculum reform for SDGs - Cendy Chaterine Manopo; Cepi Riyana; Mario Emilzoli (Universitas Pendidikan Indonesia, 2025)
This study maps the global research landscape on climate change education and curriculum reform within the SDGs framework using a bibliometric approach. A total of 133 articles indexed in Scopus (2015–2025) were analyzed with VOSviewer to identify publication trends, key authors and institutions, collaboration networks, thematic clusters, and co-citation patterns. The findings show a sharp growth in publications during 2020–2025, reflecting increasing academic attention to the nexus of climate change, education, and sustainability. Research output is dominated by the United Kingdom, the United States, and Australia, although contributions from the Global South, such as Indonesia and South Africa, are emerging. Manchester Metropolitan University and Walter Leal Filho were identified as central actors. Thematic mapping revealed five main clusters: climate change education, curriculum reform, sustainable development, environmental education, and policy. Co-citation analysis highlights two intellectual pillars: education for sustainable development and theories of pro-environmental behavior. This study provides a comprehensive overview of how climate change education is linked to curriculum reform and SDGs. Academically, it advances knowledge of research trends and intellectual foundations. In practice, it offers policymakers and curriculum developers, particularly in the Global South, insights for designing inclusive, context-specific climate change education strategies. Abstrak Penelitian ini memetakan lanskap penelitian global mengenai climate change education dan reformasi kurikulum dalam kerangka Sustainable Development Goals (SDGs) dengan pendekatan bibliometrik. Sebanyak 133 artikel terindeks Scopus periode 2015–2025 dianalisis menggunakan VOSviewer untuk mengidentifikasi tren publikasi, penulis dan institusi kunci, jaringan kolaborasi, kluster tematik, serta pola ko-sitasi. Hasil analisis menunjukkan pertumbuhan publikasi yang tajam pada periode 2020–2025, menandakan meningkatnya perhatian akademik terhadap nexus perubahan iklim, pendidikan, dan keberlanjutan. Publikasi didominasi oleh Inggris, Amerika Serikat, dan Australia, meskipun kontribusi dari Global South, termasuk Indonesia dan Afrika Selatan, mulai muncul. Manchester Metropolitan University dan Walter Leal Filho teridentifikasi sebagai aktor sentral. Pemetaan tematik mengungkap lima kluster utama, yaitu climate change education, curriculum reform, sustainable development, environmental education, dan policy. Analisis ko-sitasi menyoroti dua pilar literatur utama, yaitu education for sustainable development dan teori perilaku pro-lingkungan. Penelitian ini memberikan gambaran komprehensif mengenai keterkaitan pendidikan iklim, reformasi kurikulum, dan SDGs. Secara akademis, penelitian ini memperkaya pengetahuan tentang tren dan fondasi intelektual riset. Secara praktis, hasilnya dapat menjadi acuan bagi pembuat kebijakan dan pengembang kurikulum, khususnya di Global South, untuk merancang strategi pendidikan iklim yang inklusif dan kontekstual. Kata Kunci: pendidikan perubahan iklim; reformasi kurikulum; SDGs; sustainable development goals